2020
DOI: 10.1111/and.13527
|View full text |Cite
|
Sign up to set email alerts
|

Second cycle of intralesional Collagenase Clostridium histolyticum for Peyronie's disease using the modified shortened protocol: Results from a retrospective analysis

Abstract: The purpose of this study was to evaluate the effectiveness and safety of the second cycle of Collagenase Clostridium histolyticum injections using the modified shortened protocol. We performed a retrospective analysis on patients who had already undergone the first cycle of injections using the modified shortened protocol and requested more injections to improve the remaining curvature. The International Index of Erectile Function, the Peyronie's Disease Questionnaire and the Global Assessment of Peyronie's D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…[17][18][19][20] Non-steroidal anti-inflammatory drugs (NSAIDs), penile traction therapy (PTT), collagenases, and shortening or lengthening surgical procedures are some treatment options for PD. [21][22][23][24] In recent years, ESWT has proven to be an effective treatment in selected patients with ED and PD, to improve erectile function and relieve penile pain, respectively. [4][5][6] ESWT is generally described as a safe andrological procedure characterized by mild and transient side effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19][20] Non-steroidal anti-inflammatory drugs (NSAIDs), penile traction therapy (PTT), collagenases, and shortening or lengthening surgical procedures are some treatment options for PD. [21][22][23][24] In recent years, ESWT has proven to be an effective treatment in selected patients with ED and PD, to improve erectile function and relieve penile pain, respectively. [4][5][6] ESWT is generally described as a safe andrological procedure characterized by mild and transient side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Oral PDE5Is, intracavernous or topical alprostadil, vacuum devices, and penile prostheses are some therapeutic options for ED 17–20 . Non‐steroidal anti‐inflammatory drugs (NSAIDs), penile traction therapy (PTT), collagenases, and shortening or lengthening surgical procedures are some treatment options for PD 21–24 . In recent years, ESWT has proven to be an effective treatment in selected patients with ED and PD, to improve erectile function and relieve penile pain, respectively 4–6 …”
Section: Discussionmentioning
confidence: 99%
“…Capece et al reported that 5/17 patients receiving the second cycle of three injections had a further improvement of the curvature. 16 Following treatment with CCH, only two (3%) patients underwent cavernoplication because of disappointing results.…”
Section: Discussionmentioning
confidence: 99%
“…10 The modified scheme introduced by Abdel Raheem et al contained three injections 4 weeks apart during 3 months together with the use of a vacuum erection device (VED) twice daily, stretching the penis five times for 2 min. [12][13][14][15][16][17] The treatment of PD with CCH in the acute phase showed good results, even with a single injection. [18][19][20] Treatment with CCH in patients with stable PD has been…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation